Families in Nigeria : understanding their diversity, adaptability, and strengths - Fawole, Olufemi Adeniyi; Blair, Sampson Lee (Contemporary perspectives on family research ;, 2022)
With the largest population in Africa, Nigeria truly embodies the concept of diversity. Home to hundreds of different ethnic groups, speaking an equal number of languages, and each bearing their own specific norms and values, Nigerian families exist across virtually the entire spectrum of size and structure and maintain unique family ties which have endured the nation's long and complicated history. This collection focuses upon the diversity, adaptability, and strengths of Nigerian families. Examining intimate relationships, both preceding and within the context of marriage, as well as the particular dynamics among family members, this volume investigates how Nigerian families have responded to societal factors, modernization, and change. Societal factors, such as increasing conservatism, poverty, unemployment, and the like have created considerable strains, yet Nigerian families have shown a particular ability to adapt to and overcome many of these problems, thus revealing their substantial strengths.